Performance analysis of a water desalination system using humidification and dehumidification techniques with thermoelectric cooling unit - Ali M. Ashour; Saif Ali Kadhim; Moafaq K.S. Al-Ghezi; Issa Omle; Ravishankar Sathyamurthy (Case Studies in Thermal Engineering, 2025)
In this paper, a humidification and dehumidification (HDH) desalination system is developed using an evaporative pad and thermoelectric cooling (TEC) units to condense water vapor to increase water production with minimum energy consumption. In contrast to typical HDH systems, which are based on natural heat sources or external condensers, the intended approach forms a thermally coupled setup where air humidification is improved by the evaporative pad, whilst the TEC modules provide localized condensation through preserving a cold sink surface simultaneously. The investigation was concentrated on the major operating conditions, such as air velocity (0.5–5 m/s), input voltage of the TEC (5–16 V), and seasonal environmental conditions, to assess the performance of the system as per water productivity, coefficient of performance (COP), gain output ratio (GOR), recovery ratio (RR), and effectiveness. The optimum performance is at 9 V and air velocity of 0.5–1.0 m/s, where equilibrium between electrical consumption and cooling capacity is established. The system produced daily fresh water anywhere between 1400 mL/day when it was hot and dry and 1800 mL/day when it was cooler and more humid. The maximum indicated GOR was 1.374, and the maximum COP of approximately 0.78 under optimal conditions was observed. The daily performance was the best in the morning and evening, when lower temperatures and higher humidities enhanced efficiency of condensation. The research gives us clues to improve the performance of the HDH system under optimized operating conditions.